An Investigation of Ergative Construction in Targhy Accent of Rajy Dialect from Distributed Morphology Viewpoint - Tayebeh Asadi Mofarah; Mozhgan Asghary Targhy (زبان پژوهی, 2022)
Ergative construction (EC) as a subtle characteristic of Iranian languages and dialects has massively fostered a large body of research in the literature over previous decades. In this regard, the current study focuses on the morphotactics of the verb construction and the manner through which ergative alignment is formed in Targhy accent of Rajy dialect of which description and explanation of language behavior in the area in question have been entirely overlooked from distributed morphology (DM) viewpoint. Generally speaking, EC, according to Karimi’s (2012a) generalization, in all Iranian and dialects can be classified into two categories. In the first group including North Kurdish and Baluchi, there is an agreement relation between the direct object and the T head represented by a verbal agreement (VA) at the end of the verb. In his proposal, in the EC of the second class including Central Kurdish and Larestani, which based on the current article, Traghy is of their pattern as well, however, there is no agreement in that oblique pronominal clitics (PCLs), which enter as a big DP form in the syntactic derivation, function as interveners, blocking any conceivable agreement between T head and a direct object altogether. Plus, there exists a complementary distribution between Vas and oblique PCLs, Karimi (ibid) says. He asserts, without any agreement relation with T, oblique PCLs just double φ-features of the subject, and the PCLs function as a repair strategy in response to the loss of oblique (here ERG) case marker, whereas EC still exists dynamically. Nonetheless, this article, based on both empirical and theoretical evidence, argues that contra to Karimi’s (2012a) generalization it seems fair to suggest at least in EC of Targhy, which in turn bears the pattern of the second category, there is a genuinely fullfledged agreement in place, while agreement exponents, be it VAs or agreement clitics (ACLs) have no complementary distribution with their oblique PCL counterparts whatsoever.